Philippine directory of foundations - Lim, Narzalina Z.; Association of Foundations (Manila The SCC Development and Research Foundation, 1974)
The product of the first attempt to compile a Philippine Directory of Foundations, the directory includes 131 foundations. Information on each foundation includes: address, date of establishment, date of NSDB certification(if NSDB-certified foundation), objectives and purposes, modes of activity, field of interest, financial data in regard to net assets and income, and information on the internal organization of the foundations.
The foundations are listed in alphabetical order. They are also classified according to fields of activity. The directory aims to serve as a means of communication and coordination among foundations in the Philippines.
Keywords: Charitable uses, trusts, and foundations -- Philippines -- Directories